Pengaruh Pembatasan Protein Pada Umur Dini Terhadap Performan Ayam Broiler - Sulaiman Ibrahim (Jurnal Agripet, 2001)
ABSTRACT. An experiment was conducted for six weeks to study the effect of early restricted protein on performance of broiler in 96 three days old Hubbard chicks. This number of birds were randomly divided into three experimental groups, each consisting of 32 birds was divides into four replications of 8 birds. Which were then placed into 55 x 50 x 50 cm cages at the rate of four birds per cage. Group one, two and three were fed 24%, 20%, and 16% crude protein respectively fot the first 3 weeks, and four the second 3 weeks all groubs were fed 20% crude protein. All birds were maintained with feed and water always available. The amount of feed consumption each week during the experiment was recorded. The initial weight of each bird was recorded at the beginning of the experiment. At the first 3 weeks 16% crude protein decreased weight gains and feed efficiency of chickens significantly (P 0.05) below that of the 20% and 24% crude protein groups. However, at the second three weeks there were no significant differences among the three groups of birds. There were no significant differences among the groups of birds in feed consumption during the six weeks of the experiment.